Bacteriological analysis of isolated chronic sinusitis without polyps - Stryjewska-Makuch, Grażyna (Postepy Dermatol Alergol, 2018)
INTRODUCTION: Chronic sinusitis (CRS) is phenotypically divided into inflammation with polyps (CRSwNP) or without polyps (CRSsNP). AIM: To try to explain the reasons for isolated sinusitis by analysing medical history as well as anatomical and bacteriological data. MATERIAL AND METHODS: In 2016, endoscopic surgery was performed in 103 patients with CRSsNP within 6 months. The authors evaluated 28 patients with lesions in one sinus. RESULTS: The patients did not report any previous facial trauma, dental procedures, there were no odontogenic causes of the disease. They had not been treated with antibiotics within 30 days prior to admission to hospital. Ninety-seven bacterial strains were grown, of which 32 in patients with isolated nasal sinusitis. Statistical analysis has shown that there is a trend toward a statistically significant (p = 0.0868) relationship between the presence of Staphylococcus aureus and the type of inflammation. CONCLUSIONS: There is an indication that the presence of Staphylococcus aureus is associated with isolated sinusitis, especially in women.